Effect of Recrystallization Annealing on the Inelastic Properties of TiNi Alloy under Bending; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Grishkov V. N.; Lotkov A. I.; Baturin A. A. Anatoly Anatolievich; Cherniavsky A. G.; Timkin V. N.; Zhapova D. Yu. (2016, 2016)
Title screen